Narrative production skills of language minority learners and their English-only classmates in early adolescence. (1st September 2015) - GÁMEZ, PERLA B.; LESAUX, NONIE K.; RIZZO, ANDREA ANUSHKO
ABSTRACT: This study investigated the narrative production skills of early-adolescent, Spanish-speaking language minority (LM) learners ( n = 43) and their English-only (EO) peers ( n = 38). The sample was born in the United States, educated in English, and representative of low- and high-income backgrounds. Using a picture book as a prompt, students' narratives were transcribed, coded, and compared on macrostructure skills (story structure), microstructure skills (discrete language skills: vocabulary and grammar), and use of mazes (disruptions in speech). Results demonstrated that the groups did not differ on story structure. However, LM learners produced lengthier narratives than their EO peers, ones that resulted in stories that were less grammatically diverse and included more grammatical revisions and errors in prepositions. Thus, by early adolescence, EO and LM learners in urban schools may have well-developed macrostructure skills, yet the LM learners may still be developing specific microstructure skills.